THE MAPPING POLITICAL OF IDENTITY IN LOCAL ELECTION OF NORTH MALUKU 2013 - Kambo, Gustiana (Universitas Muhammadiyah Yogyakarta, 2018)
The interpretation of identity politics as a source and political means in the implementation of the election is well recognized by the candidates for regional head. In the Local Election North Maluku Â 2013 identity politics occurs at the practical level that is used as a tool-manipulation tool to raise political power to achieve an interest. This study looks at how the mapping of identity politics ethnic and religious backgrounds that occurred in North Maluku election in 2013. This research uses qualitative research methods with the type of descriptive analysis research. This research data is obtained from interviews and articles related to research conducted. The results of this study indicate that in the election there is a mapping of identity politics based on ethnic and religious identity. Ethnic identity and religious identity become a tool for raising political power to each candidate of regional head, so that the candidate of the head of region only excels in ethnic or religious base areas.Keywords: Identity, political identity, ethnic idenitity, religion identity.Â